Preparation method of high-strength environment-friendly foaming hot melt adhesive
By using functional fillers and stabilizers in foamed hot melt adhesives, their mechanical properties and aging resistance are improved, and the problems of low bonding strength and poor durability in high temperature and high humidity environments are solved, thereby achieving higher bonding strength and service life.
Patent Information
- Application Number
- CN202411788252.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
AI Technical Summary
The existing foamed hot melt adhesives have low bond strength in high temperature and high humidity environments, poor durability, insufficient chemical resistance, uneven density leads to insufficient local strength, and high requirements for substrate surface treatment.
Functional fillers made of polyurethane prepolymer, modified nanoTiO2 intercalated mica and 4,4'-diamino-3,3'-dimethylbiphenylmethane are used to improve the mechanical properties and aging resistance of foamed hot melt adhesives.
It significantly improves the bonding strength and service life of foamed hot melt adhesive, enhances its heat resistance and aging resistance, and solves the problems of uneven density and insufficient chemical resistance.
Smart Images

Figure BDA0005174660540000141 
Figure BDA0005174660540000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot melt adhesives, and in particular relates to a method for preparing a high-strength environmentally friendly foaming hot melt adhesive. Background Art
[0002] Hot melt adhesive is an adhesive that can flow and solidify under heating conditions to form a bond. It is heated to become a liquid and applied to the surface to be bonded. After cooling, it hardens to achieve the bonding function. Common types of hot melt adhesives include EVA, polyurethane, polyester, polyamide, etc. This adhesive is characterized by its fast curing ability and is suitable for bonding a variety of materials such as paper, wood, plastic, metal, etc. Foaming hot melt adhesive has a special property, that is, it can produce foam during the curing process. This foam can fill irregular surfaces or gaps to provide better bonding effects, while reducing weight and reducing the amount of material used. Foaming hot melt adhesive is widely used in packaging, furniture manufacturing, automotive interiors and other fields. Due to its environmentally friendly, non-toxic and easy-to-operate characteristics, it has received more and more attention and application in recent years. In addition, the performance of foaming hot melt adhesive can be optimized by adjusting the formula. To adapt to different application requirements and working environments, this makes it one of the indispensable and important materials in industrial production.
[0003] Although foaming hot melt adhesive has many advantages, it also has some shortcomings in practical applications, such as relatively low bonding strength, especially in high temperature and high humidity environments, its durability will be affected, resulting in decreased bonding strength. Foaming hot melt adhesive has poor chemical resistance, and certain solvents or chemicals can cause the colloid to soften or decompose, affecting the bonding effect. Due to the existence of the foaming process, the foaming hot melt adhesive may have uneven density after curing, resulting in insufficient local strength, especially in applications that need to withstand greater stress. This defect is particularly obvious. In addition, foaming hot melt adhesive has high requirements for the surface treatment of the substrate. If the surface cleanliness is not enough or the roughness is too large or too small, it will affect the final bonding quality.
[0004] In order to solve the above problems, the existing technology generally improves the physical properties and chemical stability of the foaming hot melt adhesive by adjusting the type and proportion of the base polymer, or adding functional additives such as toughening agents, reinforcing agents, antioxidants, etc. However, there are still some disadvantages. For example, high-performance base polymers and functional additives are usually expensive, which will lead to an increase in the cost of the final product, thus affecting its wide application; the introduction of additives will reduce the compatibility between different components, thereby affecting the stability and final performance of the foaming hot melt adhesive; after adding too many additives, the rheological properties of the foaming hot melt adhesive will change, which will affect its processing performance, such as fluidity and coating properties, and bring inconvenience to practical applications. Therefore, there is an urgent need for a high-strength and environmentally friendly foaming hot melt adhesive with excellent performance. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a high-strength environmentally friendly foamed hot melt adhesive, which further improves the mechanical properties and aging resistance of the foamed hot melt adhesive by using a functional filler made of polyurethane prepolymer, modified nano-TiO2 intercalated muscovite and 4,4'-diamino-3,3'-dimethylbiphenylmethane, and a specific stabilizer. The preparation method of the present invention is simple, and the obtained foamed hot melt adhesive has high bonding strength and long service life.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a high-strength environmentally friendly foaming hot melt adhesive, comprising the following steps:
[0008] Step (1): according to the raw material formula, 60-85 parts by weight of ethylene-vinyl acetate copolymer, 5-15 parts by weight of hydrogenated petroleum resin, 5-10 parts by weight of functional filler, 5-7 parts by weight of foaming agent, 3-5 parts by weight of lubricant, 0.5-1.5 parts by weight of cross-linking agent, 0.4-0.6 parts by weight of antioxidant, and 0.5-1.5 parts by weight of stabilizer are weighed and set aside;
[0009] Step (2): adding the raw materials weighed in step (1) into a mixer, stirring and mixing, and then feeding into an extruder for melt extrusion, and then pulverizing after cooling to obtain a masterbatch;
[0010] Step (3): The masterbatch obtained in step (2) is fed into an injection molding machine to be processed into a sample, thereby obtaining the high-strength and environmentally friendly foaming hot-melt adhesive.
[0011] The present invention effectively improves the mechanical strength and heat resistance of the foaming hot melt adhesive by adding specific functional fillers. First, after high-temperature calcination and acid treatment, the interlayer spacing of the two-dimensional layered structure of white mica is increased, which is not only conducive to the insertion of nano-TiO2, but also enhances the activity of the white mica interlayer, providing more active sites for subsequent reactions; inserting nano-TiO2 into the interlayer of white mica, on the one hand, increases the specific surface area of the functional filler, greatly increases the contact area between the filler and the matrix material, and helps to form a stronger interface interaction, which can effectively transfer stress, thereby improving the mechanical properties of the material; on the other hand, nano-TiO2 can play the role of an auxiliary cross-linking agent, help to form a cross-linking network, limit the movement of polymer chain segments, reduce the deformation of the material under stress conditions, and improve the strength of the material; and nano-TiO2 itself has good thermal stability and light aging resistance, which can enhance the heat resistance and aging resistance of the matrix material. Secondly, 3-glycidyloxypropyltriethoxysilane is used to modify the nano-TiO2 intercalated muscovite, which contains active groups that can be grafted to the surface of muscovite. At the same time, the epoxy groups it contains can react with the primary amine groups in 4,4'-diamino-3,3'-dimethylbiphenylmethane, thereby tightly bonding the polyurethane elastomer to the surface of the nano-TiO2 intercalated muscovite, allowing the functional filler to be more evenly dispersed in the matrix material, effectively avoiding the agglomeration of filler particles, and ensuring a stable and firm interface bond between the filler and the matrix, which not only helps to improve the mechanical strength of the material, but also can better improve the heat resistance of the material.
[0012] Preferably, the method for preparing the functionalized filler comprises the following steps:
[0013] 10-20 parts by weight of white mica are calcined, cooled, and then added to a sodium nitrite aqueous solution, heated and stirred, centrifuged, and dried to obtain pretreated white mica; 5-8 parts by weight of pretreated white mica are added to anhydrous ethanol for ultrasonic dispersion, and then 1-3 parts by weight of tetrabutyl titanate are added for stirring, and then 0.5-1 parts by weight of diethanolamine are added for continuous stirring, centrifuged, and dried to obtain nano-TiO2 intercalated white mica; 2-3 parts by weight of nano-TiO2 intercalated white mica are mixed with anhydrous ethanol, and then 0.3-0.5 parts by weight of 3-glycidyloxypropyltriethoxysilane are added for heating and stirring, centrifuged, and dried to obtain modified nano-TiO2 intercalated white mica;
[0014] 100-150 parts by weight of polytetrahydrofuran diol, 40-60 parts by weight of isophorone diisocyanate and 1-2 parts by weight of dibutyltin dilaurate are mixed, heated and reacted, and vacuum degassing is performed to obtain a polyurethane prepolymer; 20-30 parts by weight of polyurethane prepolymer, 1-3 parts by weight of modified nano-TiO2 intercalated muscovite and 1-2 parts by weight of 4,4'-diamino-3,3'-dimethylbiphenylmethane are mixed, heated and reacted, and cured to obtain a functional filler.
[0015] Furthermore, the method for preparing the functionalized filler comprises the following steps:
[0016] 10-20 parts by weight of white mica are calcined at 600-700° C. for 5-8 hours, cooled, then added to 300-500 parts by weight of a 3-6wt% sodium nitrite aqueous solution, stirred at 80-90° C. and 500-700 rpm for 3-5 hours, centrifuged, and dried to obtain pretreated white mica; 5-8 parts by weight of the pretreated white mica are added to 70-100 parts by weight of anhydrous ethanol, ultrasonically dispersed at 20-25 kHz and 200-300 W for 10-20 minutes, then 1-3 parts by weight of tetrabutyl titanate are added, and stirred at 2 Stirring at 2-27°C and 500-700rpm for 10-30min, adding 0.5-1 weight part of diethanolamine and continuing stirring for 3-5h, centrifuging and drying to obtain nano TiO2 intercalated muscovite; mixing 2-3 weight parts of nano TiO2 intercalated muscovite with 50-70 weight parts of anhydrous ethanol, then adding 0.3-0.5 weight part of 3-glycidyloxypropyltriethoxysilane, stirring at 50-55°C and 100-300rpm for 1-2h, centrifuging and drying to obtain modified nano TiO2 intercalated muscovite;
[0017] 100-150 parts by weight of polytetrahydrofuran diol, 40-60 parts by weight of isophorone diisocyanate and 1-2 parts by weight of dibutyltin dilaurate are mixed, reacted at 80-90°C for 1-3 hours, and vacuum degassing is performed to obtain a polyurethane prepolymer; 20-30 parts by weight of a polyurethane prepolymer, 1-3 parts by weight of modified nano-TiO2 intercalated muscovite, and 1-2 parts by weight of 4,4'-diamino-3,3'-dimethylbiphenylmethane are mixed, reacted at 75-80°C for 0.5-1.5 hours, and cured to obtain a functional filler.
[0018] Preferably, the melt mass flow rate of the ethylene-vinyl acetate copolymer is 5-10 g / 10 min, measured at 190° C. and 2.16 kg according to ASTM D1238.
[0019] Preferably, the VA content of the ethylene-vinyl acetate copolymer is 25-30%.
[0020] Preferably, the cross-linking agent is one or more of dicumyl peroxide, tert-butyl peroxyisopropyl formate, benzoyl peroxide, azobisisobutyronitrile, and triisopropyl isocyanate.
[0021] Furthermore, the cross-linking agent is dicumyl peroxide.
[0022] Preferably, the foaming agent is one or more of azodicarbonamide, p-toluenesulfonyl hydrazide, N,N'-dinitrosopentamethylenetetramine, and sodium carbonate.
[0023] Furthermore, the foaming agent is a mixture of azodicarbonamide and p-toluenesulfonyl hydrazide in a weight ratio of 0.5-1:1.
[0024] Preferably, the lubricant is one or more of microcrystalline wax, polyethylene wax, and silicone powder.
[0025] Furthermore, the lubricant is microcrystalline wax.
[0026] Preferably, the antioxidant is one or more of antioxidant CA, antioxidant 1010, antioxidant 168, antioxidant 264, and antioxidant 330.
[0027] Furthermore, the antioxidant is a mixture of antioxidant CA and antioxidant 168 in a weight ratio of 1:1-2.
[0028] Preferably, the stabilizer is one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl) ester, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, and calcium stearate.
[0029] The present invention adopts a stabilizer composed of [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butyl malonate (1,2,2,6,6-pentamethyl-4-piperidinyl) ester, 2-hydroxy-4-n-octyloxybenzophenone and calcium stearate, so as to further improve the aging resistance of the foaming hot melt adhesive; wherein, [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butyl malonate (1,2,2,6,6-pentamethyl-4-piperidinyl) ester is used as a light stabilizer, and the aging process of the material is delayed by capturing free radicals and preventing the chain oxidation reaction caused by the free radicals; 2-hydroxy-4-n-octyloxybenzophenone is used as a light absorber, and can absorb ultraviolet rays and convert them into other forms of energy, so as to prevent the ultraviolet rays from directly damaging the material; the two act synergistically, so that the foaming hot melt adhesive has a better mechanical property retention rate and a longer service life.
[0030] Furthermore, the stabilizer is a mixture of [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl), 2-hydroxy-4-n-octyloxybenzophenone and calcium stearate in a weight ratio of (0.3-0.6):(0.3-0.6):1.
[0031] Preferably, a method for preparing a high-strength environmentally friendly foaming hot melt adhesive comprises the following steps:
[0032] Step (1): according to the raw material formula, 60-85 parts by weight of ethylene-vinyl acetate copolymer, 5-15 parts by weight of hydrogenated petroleum resin, 5-10 parts by weight of functional filler, 5-7 parts by weight of foaming agent, 3-5 parts by weight of lubricant, 0.5-1.5 parts by weight of cross-linking agent, 0.4-0.6 parts by weight of antioxidant, and 0.5-1.5 parts by weight of stabilizer are weighed and set aside;
[0033] Step (2): adding the weighed raw materials of step (1) into a mixer at a rotation speed of 300-500 r / min and stirring and mixing for 20-30 min, then feeding into an extruder at an extrusion temperature of 120-140° C. for melt extrusion, and after cooling, crushing through an 80-120 mesh sieve to obtain a masterbatch;
[0034] Step (3): The masterbatch obtained in step (2) is fed into an injection molding machine and processed into a sample with a thickness of 1-3 mm, thereby obtaining the high-strength and environmentally friendly foaming hot melt adhesive.
[0035] The present invention also provides a high-strength environmentally friendly foaming hot-melt adhesive prepared by the method.
[0036] The application of the high-strength environmentally friendly foaming hot melt adhesive of the present invention includes, but is not limited to: bonding of metal materials, plastics, wood materials, and glass.
[0037] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0038] 1. The present invention provides a method for preparing a high-strength environmentally friendly foaming hot melt adhesive, which effectively improves the heat resistance and aging resistance of the foaming hot melt adhesive by using a functional filler made of polyurethane prepolymer, modified nano-TiO2 intercalated muscovite and 4,4'-diamino-3,3'-dimethylbiphenylmethane, and a stabilizer composed of [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate di(1,2,2,6,6-pentamethyl-4-piperidinyl) ester, 2-hydroxy-4-n-octyloxybenzophenone and calcium stearate, so that the foaming hot melt adhesive has excellent tensile strength and bonding strength and a long service life. The preparation method of the present invention is simple and easy to expand production.
[0039] 2. The present invention effectively improves the mechanical strength and heat resistance of the foaming hot melt adhesive by adding a functional filler made of polyurethane prepolymer, modified nano-TiO2 intercalated muscovite and 4,4'-diamino-3,3'-dimethylbiphenylmethane; inserting nano-TiO2 into the interlayer of muscovite increases the specific surface area of the functional filler, greatly increases the contact area between the filler and the matrix material, and helps to form a stronger interface interaction. These interactions can effectively transmit stress, thereby improving the mechanical properties of the material; and nano-TiO2 itself has good Good thermal stability and resistance to light aging can enhance the heat resistance and aging resistance of the matrix material; 3-glycidyloxypropyltriethoxysilane is used to modify the nano-TiO2 intercalated muscovite, so that the polyurethane elastomer is tightly bonded to the surface of the nano-TiO2 intercalated muscovite, so that the functional filler can be more evenly dispersed in the matrix material, effectively avoiding the agglomeration of filler particles, and ensuring the formation of a stable and firm interface bond between the filler and the matrix, which not only helps to improve the mechanical strength of the material, but also can better improve the heat resistance of the material.
[0040] 3. The present invention adopts a stabilizer composed of [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl) ester, 2-hydroxy-4-n-octyloxybenzophenone and calcium stearate, wherein [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl) ester is used as a light stabilizer to delay the aging process of the material by capturing free radicals and preventing the chain oxidation reaction caused by free radicals. 2-Hydroxy-4-n-octyloxybenzophenone is used as a light absorber to absorb ultraviolet rays and convert them into other forms of harmless energy to prevent direct damage to the material by ultraviolet rays. The synergistic effect of the two makes the foaming hot melt adhesive have a better mechanical property retention rate and prolongs the service life. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Ethylene-vinyl acetate copolymer, brand: EVAMV1055, melt mass flow rate: 8.0 g / 10 min (190°C / 2.16 kg, ASTM D1238), VA content: 28%, manufacturer: TPI, Thailand.
[0043] Hydrogenated petroleum resin, brand: I-MARV P100, weight average molecular weight is 660, softening point is 100℃, manufacturer: Idemitsu, Japan.
[0044] [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl) ester, CAS: 63843-89-0.
[0045] 2-Hydroxy-4-octyloxybenzophenone, CAS: 1843-05-6.
[0046] Example 1
[0047] This embodiment provides a method for preparing a high-strength environmentally friendly foaming hot melt adhesive, comprising the following steps:
[0048] Step (1): according to the raw material formula, 72 parts by weight of ethylene-vinyl acetate copolymer, 10 parts by weight of hydrogenated petroleum resin, 8 parts by weight of functional filler, 6 parts by weight of foaming agent, 4 parts by weight of lubricant, 1 part by weight of cross-linking agent, 0.5 parts by weight of antioxidant, and 1 part by weight of stabilizer are weighed and set aside;
[0049] Step (2): adding the weighed raw materials of step (1) into a mixer at a rotation speed of 400 r / min and stirring and mixing for 25 minutes, then feeding into an extruder at an extrusion temperature of 130° C. for melt extrusion, and after cooling, crushing through a 100-mesh sieve to obtain a masterbatch;
[0050] Step (3): The masterbatch obtained in step (2) is fed into an injection molding machine and processed into a sample with a thickness of 2 mm, thereby obtaining the high-strength and environmentally friendly foaming hot-melt adhesive.
[0051] The foaming agent is a mixture of azodicarbonamide and p-toluenesulfonyl hydrazide in a weight ratio of 0.8:1.
[0052] The lubricant is microcrystalline wax.
[0053] The cross-linking agent is dicumyl peroxide.
[0054] The antioxidant is a mixture of antioxidant CA and antioxidant 168 in a weight ratio of 1:1.5.
[0055] The stabilizer is a mixture of [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl), 2-hydroxy-4-n-octyloxybenzophenone and calcium stearate in a weight ratio of 0.5:0.5:1.
[0056] The method for preparing the functionalized filler comprises the following steps:
[0057] 15 parts by weight of white mica (average particle size of 400 mesh) were calcined at 650° C. for 7 h, cooled, then added to 400 parts by weight of a 4.5 wt% sodium nitrite aqueous solution, stirred at 85° C. and 600 rpm for 3.5 h, centrifuged, and dried to obtain pretreated white mica; 6 parts by weight of the pretreated white mica were added to 80 parts by weight of anhydrous ethanol, ultrasonically dispersed at 20 kHz and 300 W for 15 min, then 2 parts by weight of tetrabutyl titanate were added, and the mixture was stirred at 25 ℃, 600rpm stirring for 20min, then adding 0.8 weight parts of diethanolamine and continuing stirring for 3.5h, centrifuging and drying to obtain nano-TiO2 intercalated muscovite; 2.5 weight parts of nano-TiO2 intercalated muscovite were mixed with 60 weight parts of anhydrous ethanol, and then 0.45 weight parts of 3-glycidyloxypropyltriethoxysilane were added, stirring at 53℃, 200rpm for 1.5h, centrifuging and drying to obtain modified nano-TiO2 intercalated muscovite;
[0058] 120 parts by weight of polytetrahydrofuran diol (weight average molecular weight of 1000), 50 parts by weight of isophorone diisocyanate and 1.5 parts by weight of dibutyltin dilaurate are mixed, reacted at 86°C for 2 hours, and vacuum degassed to obtain a polyurethane prepolymer; 25 parts by weight of a polyurethane prepolymer, 2 parts by weight of modified nano-TiO2 intercalated muscovite, and 1.2 parts by weight of 4,4'-diamino-3,3'-dimethylbiphenylmethane are mixed, reacted at 78°C for 1 hour, and cured to obtain a functional filler.
[0059] Example 2
[0060] This embodiment provides a high-strength environmentally friendly foaming hot melt adhesive, comprising the following raw materials in parts by weight:
[0061] Step (1): according to the raw material formula, 60 parts by weight of ethylene-vinyl acetate copolymer, 5 parts by weight of hydrogenated petroleum resin, 5 parts by weight of functional filler, 5 parts by weight of foaming agent, 3 parts by weight of lubricant, 0.5 parts by weight of cross-linking agent, 0.4 parts by weight of antioxidant, and 0.5 parts by weight of stabilizer are weighed and set aside;
[0062] Step (2): adding the weighed raw materials of step (1) into a mixer at a rotation speed of 300 r / min and stirring for 20 min, then feeding into an extruder at an extrusion temperature of 120° C. for melt extrusion, and then pulverizing through an 80-mesh sieve after cooling to obtain a masterbatch;
[0063] Step (3): The masterbatch obtained in step (2) is fed into an injection molding machine and processed into a sample with a thickness of 1 mm, thereby obtaining the high-strength environmentally friendly foaming hot melt adhesive.
[0064] The foaming agent is a mixture of azodicarbonamide and p-toluenesulfonyl hydrazide in a weight ratio of 0.5:1.
[0065] The lubricant is microcrystalline wax.
[0066] The cross-linking agent is dicumyl peroxide.
[0067] The antioxidant is a mixture of antioxidant CA and antioxidant 168 in a weight ratio of 1:1.
[0068] The stabilizer is a mixture of [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl), 2-hydroxy-4-n-octyloxybenzophenone and calcium stearate in a weight ratio of 0.3:0.3:1.
[0069] The preparation method of the functionalized filler is the same as that of Example 1.
[0070] Example 3
[0071] This embodiment provides a high-strength environmentally friendly foaming hot melt adhesive, comprising the following raw materials in parts by weight:
[0072] Step (1): according to the raw material formula, 85 parts by weight of ethylene-vinyl acetate copolymer, 15 parts by weight of hydrogenated petroleum resin, 10 parts by weight of functional filler, 7 parts by weight of foaming agent, 5 parts by weight of lubricant, 1.5 parts by weight of cross-linking agent, 0.6 parts by weight of antioxidant, and 1.5 parts by weight of stabilizer are weighed and set aside;
[0073] Step (2): adding the weighed raw materials of step (1) into a mixer at a rotation speed of 500 r / min and stirring for 30 min, then feeding into an extruder at an extrusion temperature of 140° C. for melt extrusion, and then pulverizing through a 120-mesh sieve after cooling to obtain a masterbatch;
[0074] Step (3): The masterbatch obtained in step (2) is fed into an injection molding machine and processed into a sample with a thickness of 3 mm, thereby obtaining the high-strength and environmentally friendly foaming hot-melt adhesive.
[0075] The foaming agent is a mixture of azodicarbonamide and p-toluenesulfonyl hydrazide in a weight ratio of 1:1.
[0076] The lubricant is microcrystalline wax.
[0077] The cross-linking agent is dicumyl peroxide.
[0078] The antioxidant is a mixture of antioxidant CA and antioxidant 168 in a weight ratio of 1:2.
[0079] The stabilizer is a mixture of [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl), 2-hydroxy-4-n-octyloxybenzophenone and calcium stearate in a weight ratio of 0.6:0.6:1.
[0080] The preparation method of the functionalized filler is the same as that of Example 1.
[0081] Comparative Example 1
[0082] The difference between this comparative example and Example 1 is that the stabilizer is different, specifically as follows: the stabilizer is a mixture of [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl) and calcium stearate in a weight ratio of 1:1.
[0083] Comparative Example 2
[0084] The difference between this comparative example and Example 1 is that the stabilizer is different, specifically as follows: the stabilizer is a mixture of 2-hydroxy-4-n-octyloxybenzophenone and calcium stearate in a weight ratio of 1:1.
[0085] Comparative Example 3
[0086] The difference between this comparative example and Example 1 is that the preparation method of the functionalized filler is different, which is as follows: The preparation method of the functionalized filler comprises the following steps:
[0087] 15 parts by weight of white mica (average particle size of 400 mesh) were calcined at 650° C. for 7 hours, cooled, and then added to 400 parts by weight of a 4.5wt% sodium nitrite aqueous solution, stirred at 85° C. and 600 rpm for 3.5 hours, centrifuged, and dried to obtain pretreated white mica; 2.5 parts by weight of the pretreated white mica were mixed with 60 parts by weight of anhydrous ethanol, and then 0.45 parts by weight of 3-glycidyloxypropyltriethoxysilane were added, stirred at 53° C. and 200 rpm for 1.5 hours, centrifuged, and dried to obtain modified white mica;
[0088] 120 parts by weight of polytetrahydrofuran diol (weight average molecular weight of 1000), 50 parts by weight of isophorone diisocyanate and 1.5 parts by weight of dibutyltin dilaurate were mixed, reacted at 86°C for 2 hours, and vacuum degassed to obtain a polyurethane prepolymer; 25 parts by weight of a polyurethane prepolymer, 2 parts by weight of modified muscovite and 1.2 parts by weight of 4,4'-diamino-3,3'-dimethylbiphenylmethane were mixed, reacted at 78°C for 1 hour, and cured to obtain a functional filler.
[0089] Comparative Example 4
[0090] The difference between this comparative example and Example 1 is that the preparation method of the functionalized filler is different, which is as follows: The preparation method of the functionalized filler comprises the following steps:
[0091] 6 parts by weight of white mica (average particle size of 400 mesh) are added to 80 parts by weight of anhydrous ethanol, and ultrasonically dispersed at 20kHz and 300W for 15 minutes, and then 2 parts by weight of tetrabutyl titanate are added, and stirred at 25°C and 600rpm for 20 minutes, and then 0.8 parts by weight of diethanolamine are added and stirred for 3.5 hours, centrifuged, and dried to obtain nano-TiO2 intercalated white mica; 2.5 parts by weight of nano-TiO2 intercalated white mica are mixed with 60 parts by weight of anhydrous ethanol, and then 0.45 parts by weight of 3-glycidyloxypropyltriethoxysilane are added, and stirred at 53°C and 200rpm for 1.5 hours, centrifuged, and dried to obtain modified nano-TiO2 intercalated white mica;
[0092] 120 parts by weight of polytetrahydrofuran diol (weight average molecular weight of 1000), 50 parts by weight of isophorone diisocyanate and 1.5 parts by weight of dibutyltin dilaurate are mixed, reacted at 86°C for 2 hours, and vacuum degassed to obtain a polyurethane prepolymer; 25 parts by weight of a polyurethane prepolymer, 2 parts by weight of modified nano-TiO2 intercalated muscovite, and 1.2 parts by weight of 4,4'-diamino-3,3'-dimethylbiphenylmethane are mixed, reacted at 78°C for 1 hour, and cured to obtain a functional filler.
[0093] Comparative Example 5
[0094] The difference between this comparative example and Example 1 is that the preparation method of the functionalized filler is different, which is as follows: The preparation method of the functionalized filler comprises the following steps:
[0095] 15 parts by weight of white mica (average particle size of 400 mesh) were calcined at 650° C. for 7 hours, cooled, and then added to 400 parts by weight of a 4.5wt% sodium nitrite aqueous solution, stirred at 85° C. and 600 rpm for 3.5 hours, centrifuged, and dried to obtain pretreated white mica; 6 parts by weight of the pretreated white mica were added to 80 parts by weight of anhydrous ethanol, ultrasonically dispersed at 20kHz and 300W for 15 minutes, and then 2 parts by weight of tetrabutyl titanate were added. Stirring at 25°C and 600 rpm for 20 min, adding 0.8 parts by weight of diethanolamine and continuing stirring for 3.5 hours, centrifuging and drying to obtain nano-TiO2 intercalated muscovite; mixing 2.5 parts by weight of nano-TiO2 intercalated muscovite with 60 parts by weight of anhydrous ethanol, then adding 0.45 parts by weight of 3-aminopropyltrimethoxysilane, stirring at 53°C and 200 rpm for 1.5 hours, centrifuging and drying to obtain modified nano-TiO2 intercalated muscovite;
[0096] 120 parts by weight of polytetrahydrofuran diol (weight average molecular weight of 1000), 50 parts by weight of isophorone diisocyanate and 1.5 parts by weight of dibutyltin dilaurate are mixed, reacted at 86°C for 2 hours, and vacuum degassed to obtain a polyurethane prepolymer; 25 parts by weight of a polyurethane prepolymer, 2 parts by weight of modified nano-TiO2 intercalated muscovite, and 1.2 parts by weight of 4,4'-diamino-3,3'-dimethylbiphenylmethane are mixed, reacted at 78°C for 1 hour, and cured to obtain a functional filler.
[0097] Comparative Example 6
[0098] The difference between this comparative example and Example 1 is that the preparation method of the functionalized filler is different, which is as follows: The preparation method of the functionalized filler comprises the following steps:
[0099] 120 parts by weight of polytetrahydrofuran diol (weight average molecular weight of 1000), 50 parts by weight of isophorone diisocyanate and 1.5 parts by weight of dibutyltin dilaurate were mixed, reacted at 86°C for 2 hours, and vacuum degassed to obtain a polyurethane prepolymer; 25 parts by weight of a polyurethane prepolymer, 2 parts by weight of muscovite (average particle size of 400 meshes), and 1.2 parts by weight of 4,4'-diamino-3,3'-dimethylbiphenylmethane were mixed, reacted at 78°C for 1 hour, and cured to obtain a functional filler.
[0100] Performance Testing
[0101] The peel strength of the high-strength environmentally friendly foamed hot melt adhesives obtained in the above-mentioned examples 1-3 and comparative examples 1-6 was measured according to the standard GB / T 2790-1995; the tensile strength of the high-strength environmentally friendly foamed hot melt adhesives obtained in the above-mentioned examples 1-3 and comparative examples 1-6 was measured according to the standard GB / T 528-2009; and then a xenon lamp aging test was performed, and the test conditions were: 10 kJ / (m 2·h), 1000h, and the peel strength and tensile strength were measured again; after curing the adhesive sample for 1 week, it was placed in a constant temperature oven for heat resistance tests at different temperatures, starting from 50℃, with a heating rate of 15℃ / h, and checking for loosening and debonding every 20min, and the temperature when loosening and debonding occurred was recorded as the heat resistance temperature; the results are shown in Table 1.
[0102] Table 1: Mechanical properties and aging resistance test results
[0103]
[0104]
[0105] It can be seen from the above performance test results that the foamed hot melt adhesives prepared in Examples 1-3 have excellent mechanical strength, aging resistance and heat resistance, especially the comprehensive performance of the foamed hot melt adhesive in Example 1 is the most outstanding. This is because the present invention significantly improves the mechanical strength and heat resistance of the foamed hot melt adhesive by preparing functional fillers using a specific method, and at the same time, adds a specific combination of stabilizers to further improve the aging resistance of the foamed hot melt adhesive.
[0106] In comparison, since Comparative Examples 1-6 did not adopt the necessary technical solutions, their corresponding performance tests were significantly worse than those of Examples 1-3. Comparative Examples 1-2 did not use a specific combination of stabilizers, and Comparative Examples 3-6 did not use functionalized strong fillers prepared by a specific method. It can be seen from the results that this led to a decrease in the mechanical strength, aging resistance and heat resistance of the foamed hot melt adhesive. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.
[0107] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high-strength environmentally friendly foaming hot melt adhesive, characterized in that: The following steps are involved: Step (1): according to the raw material formula, 60-85 parts by weight of ethylene-vinyl acetate copolymer, 5-15 parts by weight of hydrogenated petroleum resin, 5-10 parts by weight of functional filler, 5-7 parts by weight of foaming agent, 3-5 parts by weight of lubricant, 0.5-1.5 parts by weight of cross-linking agent, 0.4-0.6 parts by weight of antioxidant, and 0.5-1.5 parts by weight of stabilizer are weighed and set aside; The functional filler is obtained by reacting polyurethane prepolymer, modified nano-TiO2 intercalated muscovite and 4,4'-diamino-3,3'-dimethylbiphenylmethane; Step (2): adding the raw materials weighed in step (1) into a mixer, stirring and mixing, and then feeding into an extruder for melt extrusion, and then pulverizing after cooling to obtain a masterbatch; Step (3): The masterbatch obtained in step (2) is fed into an injection molding machine to be processed into a sample, thereby obtaining the high-strength and environmentally friendly foaming hot-melt adhesive.
2. The method for preparing the high-strength environmentally friendly foaming hot melt adhesive according to claim 1, characterized in that: The method for preparing the functionalized filler comprises the following steps: 10-20 parts by weight of muscovite are calcined, cooled, then added into a sodium nitrite aqueous solution, heated and stirred, centrifuged, and dried to obtain pretreated muscovite; 5-8 parts by weight of pretreated muscovite are added to anhydrous ethanol for ultrasonic dispersion, and then 1-3 parts by weight of tetrabutyl titanate are added for stirring, and then 0.5-1 parts by weight of diethanolamine are added for continuous stirring, centrifuged, and dried to obtain nano-TiO2 intercalated muscovite; Mix 2-3 parts by weight of nano-TiO2 intercalated muscovite with anhydrous ethanol, then add 0.3-0.5 parts by weight of 3-glycidyloxypropyltriethoxysilane, heat and stir, centrifuge, and dry to obtain modified nano-TiO2 intercalated muscovite; 100-150 parts by weight of polytetrahydrofuran diol, 40-60 parts by weight of isophorone diisocyanate and 1-2 parts by weight of dibutyltin dilaurate are mixed, heated and reacted, and vacuum degassing is performed to obtain a polyurethane prepolymer; 20-30 parts by weight of polyurethane prepolymer, 1-3 parts by weight of modified nano-TiO2 intercalated muscovite and 1-2 parts by weight of 4,4'-diamino-3,3'-dimethylbiphenylmethane are mixed, heated and reacted, and cured to obtain a functional filler.
3. The method for preparing the high-strength environmentally friendly foaming hot melt adhesive according to claim 2, characterized in that: The method for preparing the functionalized filler comprises the following steps: 10-20 parts by weight of white mica are calcined at 600-700° C. for 5-8 hours, cooled, and then added to 300-500 parts by weight of a 3-6wt% sodium nitrite aqueous solution, stirred at 80-90° C. and 500-700 rpm for 3-5 hours, centrifuged, and dried to obtain pretreated white mica; 5-8 parts by weight of pretreated muscovite are added to 70-100 parts by weight of anhydrous ethanol, and ultrasonically dispersed at 20-25kHz and 200-300W for 10-20 minutes, and then 1-3 parts by weight of tetrabutyl titanate are added, and stirred at 22-27°C and 500-700rpm for 10-30 minutes, and then 0.5-1 parts by weight of diethanolamine are added and stirred for 3-5 hours, centrifuged, and dried to obtain nano-TiO2 intercalated muscovite; Mix 2-3 parts by weight of nano-TiO2 intercalated muscovite with 50-70 parts by weight of anhydrous ethanol, then add 0.3-0.5 parts by weight of 3-glycidyloxypropyltriethoxysilane, stir at 50-55° C. and 100-300 rpm for 1-2 hours, centrifuge, and dry to obtain modified nano-TiO2 intercalated muscovite; 100-150 parts by weight of polytetrahydrofuran diol, 40-60 parts by weight of isophorone diisocyanate and 1-2 parts by weight of dibutyltin dilaurate are mixed, reacted at 80-90°C for 1-3 hours, and vacuum degassing is performed to obtain a polyurethane prepolymer; 20-30 parts by weight of a polyurethane prepolymer, 1-3 parts by weight of modified nano-TiO2 intercalated muscovite, and 1-2 parts by weight of 4,4'-diamino-3,3'-dimethylbiphenylmethane are mixed, reacted at 75-80°C for 0.5-1.5 hours, and cured to obtain a functional filler.
4. The method for preparing the high-strength environmentally friendly foaming hot melt adhesive according to claim 1, characterized in that: The stabilizer is one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl), 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, and calcium stearate.
5. The method for preparing the high-strength environmentally friendly foaming hot melt adhesive according to claim 4, characterized in that: The stabilizer is a mixture of [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate (1,2,2,6,6-pentamethyl-4-piperidinyl), 2-hydroxy-4-n-octyloxybenzophenone and calcium stearate in a weight ratio of (0.3-0.6):(0.3-0.6):
1.
6. The method for preparing the high-strength environmentally friendly foaming hot melt adhesive according to claim 1, characterized in that: The cross-linking agent is one or more of dicumyl peroxide, tert-butyl peroxy isopropyl formate, benzoyl peroxide, azobisisobutyronitrile, and triisopropyl isocyanate.
7. The method for preparing the high-strength environmentally friendly foaming hot melt adhesive according to claim 1, characterized in that: The foaming agent is a mixture of azodicarbonamide and p-toluenesulfonyl hydrazide in a weight ratio of 0.5-1:
1.
8. The method for preparing the high-strength environmentally friendly foaming hot melt adhesive according to claim 1, characterized in that: The lubricant is one or more of microcrystalline wax, polyethylene wax and silicone powder.
9. The method for preparing the high-strength environmentally friendly foaming hot melt adhesive according to claim 1, characterized in that: The antioxidant is a mixture of antioxidant CA and antioxidant 168 in a weight ratio of 1:1-2.
10. A high-strength environmentally friendly foaming hot melt adhesive prepared according to the method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Sheet mineral and nano titanium dioxide intercalating composite material and preparation method thereof
CN103950944A
Foamable hot melt adhesive compositions and use thereof
US20150322301A1